2024
DOI: 10.3390/toxics12010046
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Silico Analysis of the Bindings between Legacy and Novel Per- and Polyfluoroalkyl Substances and Human Serum Albumin

Yuqing Wu,
Jia Bao,
Yang Liu
et al.

Abstract: Per- and polyfluoroalkyl substances (PFASs) are emerging contaminants of concern that can enter the human body through a variety of pathways and thereby cause harmful effects. Exposure of pregnant women to PFASs could even affect both the mother and the child. Human serum albumin (HSA) is considered to be the primary transport protein for a variety of substances in body fluids. It can be bound to different contaminants and might result in possible effects on human health. Yet, few studies are available on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…The reactions are presented as 1 : 1, although they could be more intricate; despite multiple binding sites in BSA and other serum albumins for small molecule ligands, a number of reports have indicated 1 : 1 or predominantly 1 : 1 complexes are present. This is reported not only for PFAS 31,69,70 but also other small molecules such as flavonoids. 71 Binding studies conducted in solution have shown that PFOA has one highaffinity binding site and three low affinity binding sites in serum albumin.…”
Section: Calculation Of Association Constants For Pfoa Complexationmentioning
confidence: 59%
See 1 more Smart Citation
“…The reactions are presented as 1 : 1, although they could be more intricate; despite multiple binding sites in BSA and other serum albumins for small molecule ligands, a number of reports have indicated 1 : 1 or predominantly 1 : 1 complexes are present. This is reported not only for PFAS 31,69,70 but also other small molecules such as flavonoids. 71 Binding studies conducted in solution have shown that PFOA has one highaffinity binding site and three low affinity binding sites in serum albumin.…”
Section: Calculation Of Association Constants For Pfoa Complexationmentioning
confidence: 59%
“…31 Recently, Wu et al , have reported a 1 : 1 binding ratio of PFOA and serum albumin. 70 Hence, we assume a 1 : 1 combination for our study.PFOA + BSA ⇌ PFOA-BSAPFOA + β-CD ⇌ PFOA-β-CD…”
Section: Resultsmentioning
confidence: 99%